Don't Exceed but Evaluate

Calculus Level 4

lim n n n 2 [ ( n + 1 ) ( n + 1 2 ) ( n + 1 4 ) ( n + 1 2 n 1 ) ] n \displaystyle \lim_{n \to \infty} n^{-n^2} \Bigg [ \bigg (n + 1 \bigg ) \left (n+ \frac 1 2 \right ) \left (n + \frac 1 4 \right ) \ldots \left ( n + \frac {1}{2^{n-1}} \right ) \Bigg ]^n

If the above limit equals to α \alpha , what is the value of 1000 α \lfloor 1000 \alpha \rfloor ?


The answer is 7389.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Joel Yip
Mar 21, 2015

First lets use the identity n n 2 = ( n n ) n { n }^{ -{ n }^{ 2 } }={ \left( { n }^{ -n } \right) }^{ n } then, lim n ( n n ( n + 1 ) ( n + 1 2 ) ( n + 1 4 ) . . . ( n + 1 2 n 1 ) ) n = lim n ( ( 1 + 1 n ) ( 1 + 1 2 n ) ( 1 + 1 4 n ) . . . ( 1 + 1 2 n 1 n ) ) n = lim n ( 1 + 1 n ) n × lim n ( 1 + 1 2 n ) n × lim n ( 1 + 1 4 n ) n × . . . \lim _{ n\rightarrow \infty }{ { \left( { n }^{ -n }\left( n+1 \right) \left( n+\frac { 1 }{ 2 } \right) \left( n+\frac { 1 }{ 4 } \right) ...\left( n+\frac { 1 }{ { 2 }^{ n-1 } } \right) \right) }^{ n } } \\ =\lim _{ n\rightarrow \infty }{ { \left( \left( 1+\frac { 1 }{ n } \right) \left( 1+\frac { 1 }{ 2n } \right) \left( 1+\frac { 1 }{ 4n } \right) ...\left( 1+\frac { 1 }{ { 2 }^{ n-1 }n } \right) \right) }^{ n } } \\ =\lim _{ n\rightarrow \infty }{ { \left( 1+\frac { 1 }{ n } \right) }^{ n } } \times \lim _{ n\rightarrow \infty }{ { \left( 1+\frac { 1 }{ 2n } \right) }^{ n } } \times \lim _{ n\rightarrow \infty }{ { \left( 1+\frac { 1 }{ 4n } \right) }^{ n } } \times ...

What is lim n ( 1 + 1 a n ) n \lim _{ n\rightarrow \infty }{ { \left( 1+\frac { 1 }{ an } \right) }^{ n } } ?

Simple, lim n ( 1 + 1 a n ) n = lim n e n ln ( 1 + 1 a n ) = lim n e ln ( 1 + 1 a n ) 1 n = lim n e 1 a ( 1 n 2 ) ln ( 1 + 1 a n ) 1 n 2 = lim n e 1 a ln ( 1 + 1 a n ) = e 1 a \lim _{ n\rightarrow \infty }{ { \left( 1+\frac { 1 }{ an } \right) }^{ n } } \\ =\lim _{ n\rightarrow \infty }{ { e }^{ n\ln { \left( 1+\frac { 1 }{ an } \right) } } } \\ =\lim _{ n\rightarrow \infty }{ { e }^{ \frac { \ln { \left( 1+\frac { 1 }{ an } \right) } }{ \frac { 1 }{ n } } } } \\ =\lim _{ n\rightarrow \infty }{ { e }^{ \frac { \frac { 1 }{ a } \left( -\frac { 1 }{ { n }^{ 2 } } \right) \ln { \left( 1+\frac { 1 }{ an } \right) } }{ -\frac { 1 }{ { n }^{ 2 } } } } } \\ =\lim _{ n\rightarrow \infty }{ { e }^{ \frac { 1 }{ a } \ln { \left( 1+\frac { 1 }{ an } \right) } } } \\ ={ e }^{ \frac { 1 }{ a } }

So, e 1 e 1 2 e 1 4 . . . = e 1 + 1 2 + 1 4 + . . . = e 2 { e }^{ 1 }{ e }^{ \frac { 1 }{ 2 } }{ e }^{ \frac { 1 }{ 4 } }...\\ ={ e }^{ 1+\frac { 1 }{ 2 } +\frac { 1 }{ 4 } +... }\\ ={ e }^{ 2 }

and e 2 { e }^{ 2 } is 7.389... so the answer is 7390.

Nice solution method, Joel. I'm a little concerned about the steps taken to get to the e 1 a e^{\frac{1}{a}} result, even though that is indeed to correct result. Another approach would be

lim n ( 1 + 1 a n ) n = \lim_{n \rightarrow \infty} \left( 1 + \dfrac{1}{an} \right) ^{n} =

lim n ( ( 1 + 1 a n ) a n ) 1 a = ( lim n ( 1 + 1 a n ) a n ) 1 a . \lim_{n \rightarrow \infty} \left( \left( 1 + \dfrac{1}{an} \right)^{an} \right) ^{\frac{1}{a}} = \left(\lim_{n \rightarrow \infty} \left(1 + \dfrac{1}{an} \right)^{an} \right)^{\frac{1}{a}}.

Now let u = a n . u = an. Then u u \rightarrow \infty as n n \rightarrow \infty , and so our expression becomes

( lim u ( 1 + 1 u ) u ) 1 a = e 1 a . \left( \lim_{u \rightarrow \infty} \left(1 + \dfrac{1}{u} \right)^{u} \right) ^{\frac{1}{a}} = e^{\frac{1}{a}}.

Brian Charlesworth - 6 years, 2 months ago

Log in to reply

Thanks I noticed my error.

Joel Yip - 6 years, 2 months ago

did the same process....!!!!! ;)

Trishit Chandra - 6 years, 2 months ago
Haroun Meghaichi
Mar 23, 2015

We can rewrite the limit as exp lim n n k = 1 n 1 ln ( 1 + 1 n 2 k ) . \exp \lim_{n\to \infty} n \sum_{k=1}^{n-1} \ln\left(1+\frac{1}{n2^k} \right). Use ln ( 1 + x ) = x + o ( x ) \ln(1+x)=x+o(x) (Taylor series around zero), to get
n k = 1 n 1 ln ( 1 + 1 n 2 k ) = ( k = 1 n 1 1 2 k ) + o ( 1 ) n \sum_{k=1}^{n-1} \ln\left(1+\frac{1}{n2^k} \right) =\left( \sum_{k=1}^{n-1}\frac{1}{2^k} \right)+o(1) Then the limit is e 2 e^2 .

EXACTLY the same approach!!!

Aaghaz Mahajan - 1 year ago

I used L'Hopital's rule in step 4, and cancelled -1/n^2 in step 5. floor(1000 * e^2) = 7389

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...